Impact of various boiling intervals on the antimicrobial efficacy and phytochemical profile of selected crude aqueous plant extracts, used by Bapedi Traditional Healers in the treatment of sexually transmitted infections - Erasmus, Lourens Johannes Christoffel (My University, 2014)
Refer to document
Thesis (Ph. D. (Botany)) -- University of Limpopo, 2014
Keywords: Aqueous plant extracts; Bapedi Traditional Healers; sexually transmitted infections; Medicinal plants -- South Africa -- Limpopo.; Plant extracts.; Sexually transmitted diseases.; Healers.